Composting of the invasive species Arundo donax with sewage and agri-food sludge: Agronomic, economic and environmental aspects. (August 2018) - Pelegrín, M.; Sáez-Tovar, J.A.; Andreu-Rodríguez, J.; Pérez-Murcia, M.D.; Martínez-Sabater, E.; Marhuenda-Egea, F.C.; Pérez-Espinosa, A.; Bustamante, M.A.; Agulló, E.; Vico, A.; Paredes, C.; Moral, R.
Highlights: Different co-composting strategies using Arundo donax and sludge were validated. Exothermic index EXI2 was defined in order to compare co-composting processes. Process development and compost recalcitrance were assessed with thermal analysis. Economic estimation of NPK elements in compost was stablished. Abstract: This work evaluates several co-composting scenarios based on the use of Arundo donax biomass (AD) as bulking agent for the co-composting of sewage sludge (MS) and agri-food sludge (AS), to manage these organic wastes and to produce balanced organic fertilizers by optimizing the process. For this, six piles were prepared in commercial composting conditions, using AD in a range of 40%–80% (on a dry weight basis). Physico-chemical and chemical parameters and the thermal behaviour were evaluated during the process, as were the physical and chemical parameters of the final composts. The proportion of AD in the mixtures has a significant effect on the development of the thermophilic stage of composting, showing the piles with higher proportion of AD a quicker organic matter degradation. In addition, the evolution of the thermal indices R1 and R2 was different depending on the origin of the sludge used, indicating an increase in the relative concentration of more recalcitrant materials in the piles prepared with AS. The estimation of the global warming potential showed that the use of higher proportion of AD in the composting mixture may be a strategy to mitigate the emission of greenhouse gases during the composting process. Moreover, the end-products obtained had an additional marketable value, with a balanced nutrient content and a good degree of maturity, which indicates the viability of the composting process as a method for the stabilization of these organic wastes.